2013
DOI: 10.1016/j.reseneeco.2013.02.005
|View full text |Cite
|
Sign up to set email alerts
|

The economics of oil, biofuel and food commodities

Abstract: We study the effects on the food market of the introduction of biofuels as a substitute for fossil fuel in the energy market. We consider a world economy with an oil cartel and a competitive fringe of farmers producing energy in the form of biofuels. Farmers also produce food and sell it on the world food market. We determine the resulting relationship between prices in the energy and food markets and characterize the cartel's extraction path and the price path of energy. We show that the price of food will be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 20 publications
1
18
0
1
Order By: Relevance
“…A utilização de alternativas para a produção de energia também auxilia a economia e o reaproveitamento de resíduos de produção agrícola e/ou agroindustriais, como palha de milho, sabugo de milho, casca de arroz, casca de café, bagaço de cana-de-açúcar, casca de soja entre outros resíduos ou subprodutos que possam vir a ser utilizados como matéria-prima para biocombustíveis ou bioenergia [3,4,5,6].…”
Section: Introductionunclassified
“…A utilização de alternativas para a produção de energia também auxilia a economia e o reaproveitamento de resíduos de produção agrícola e/ou agroindustriais, como palha de milho, sabugo de milho, casca de arroz, casca de café, bagaço de cana-de-açúcar, casca de soja entre outros resíduos ou subprodutos que possam vir a ser utilizados como matéria-prima para biocombustíveis ou bioenergia [3,4,5,6].…”
Section: Introductionunclassified
“…As pointed out by [25], prior to 2008, there is little work making the link between climate policies and exhaustible resources when policies are non-optimal or international agreements are incomplete. 2 Recent dynamic models that depict the adverse response of resource extracting firms to anticipation of taxes or substitute production include [41,42,25,11,17,12]. Hoel [25] assumes that carbon resources remain cheaper than the substitute and analyses the situation where different countries have climate policies of different ambition levels.…”
Section: Introductionmentioning
confidence: 99%
“…4 For static analysis of energy substitution, see [21,44,31,32,3,34]. Bahel et al [2] developed a dynamic model but their focus was on food prices. 5 Fischer and Salant [14] examined the Green Paradox in the presence of a subsidy for renewable resources.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Matesanz et al (2014) observe a persistent increase in the degree of co-movement of the commodity prices from mid-2008 to the end of 2009, particularly for metals, oil, grains, and oilseeds, and Bahel et al (2013) find high correlation between oil prices and food prices. The 2014 oil price collapse showed that these regulations failed to prevent inefficient oil price reactions to non-fundamental factors, yet, it is unlikely to have any further tightening of regulations, simply because the oil price collapsed, which actually had a positive effect on general consumption.…”
Section: Discussionmentioning
confidence: 99%
“…It is particularly interesting to note that the oil bust of 2014 was completely unexpected, since the price collapse was not preceded by the spike, as it was the case in 1991 and 2008 -the price of crude oil just simply collapsed from a gradually rising uptrend. Thus, it is very important to understand the potential causes and consequences of the 2014 oil price collapse, especially given that the literature documents significant linkages between the oil prices and the financial markets, the macroeconomic cycle, and more specifically inflation, (see Hamilton, 1983Hamilton, , 2003Mork, 1989;Oladosu, 2009;Barsky and Kilian, 2004;Gómez-Loscos et al, 2012;Defina and Taylor, 1993;Soucek and Todorova, 2013).…”
Section: Introductionmentioning
confidence: 99%